PENDETEKSIAN PERILAKU HERDING PADA PASAR SAHAM INDONESIA DAN ASIA PASIFIK (Detection of Herding Behavior on Indonesia and Asia Pacific Stock Market) - . Gunawan; Hari Wijayanto; Noer Azam Achsani; La Ode Abdul Rahman (FORUM STATISTIKA DAN KOMPUTASI, 2011)
Herding  Behavior  is  an  irrational  investor  behavior, because  investors  do  not make investment decisions based on economic fundamentals of  risky assets, but based  on  others  investor  in  the  same  condition,  or  following  market  consensus. Herding  behavior  indications  can  be  seen  from  relation  between  dispersion  of stock  return  (Cross  Sectional  Absolute  Deviation,  CSAD)  and  market  portfolio return. If herding behavior exist, CSAD increases lower than increase of market portfolio  return  moreover,  CSAD  will  decrease  even  though  market  portfolio return increases. Herding behavior in stock market can trigger mislead in stock pricing  because  is  bias  among  investors  in  analyzing  risk  and  return.  To understand  relationship  between  CSAD  and  market  portfolio  return  in  some conditions, Quantil regression is used. Result gained from this research is that in Indonesian  and  global  Asia  Pacific  stock  market,  herding  behavior  occurs  in  a market stress condition, whereas in normal condition or in condition of very high stock return, investor behavior tends to be more rational.  Keywords : herd behavior, Quanrtile regression, CSAD